2020
DOI: 10.18699/vj20.673
|View full text |Cite
|
Sign up to set email alerts
|

The cell cycle regulatory gene polymorphisms TP53 (rs1042522) and MDM2 (rs2279744) in lung cancer: a meta-analysis

Abstract: Lung cancer is one of the most common types of cancer in the world. Although the mechanism of lung cancer is still unknown, a large number of studies have found a link between gene polymorphisms and the risk of lung cancer. The tumor suppressor p53 plays a crucial role in maintaining genomic stability and tumor prevention. MDM2 is a critical regulator of the p53 protein. Despite the importance of p53 pathway in cancer, data on the contribution of SNPs of TP53 (rs1042522) and MDM2 (rs2279744) to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been observed that common, low‐penetrance genetic polymorphisms in or near genes harbouring high‐penetrance germline mutations are associated with the genetic susceptibility to develop cancer. For example, the CHEK2 and BRCA1 genes for breast cancer, 11 the TERT gene for melanoma, 12 the CDKN2A/2B genes for PDAC and pancreatic neuroendocrine tumours 13,14 and the p53 gene for multiple cancers have both high‐penetrance and low‐penetrance variants that contribute to the disease risk 15‐18 . Even though this phenomenon is not widespread, at least according to the current literature, exploring common variants in genes known to harbour high‐penetrance variants in PDAC could still be valuable for understanding the risk of developing PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that common, low‐penetrance genetic polymorphisms in or near genes harbouring high‐penetrance germline mutations are associated with the genetic susceptibility to develop cancer. For example, the CHEK2 and BRCA1 genes for breast cancer, 11 the TERT gene for melanoma, 12 the CDKN2A/2B genes for PDAC and pancreatic neuroendocrine tumours 13,14 and the p53 gene for multiple cancers have both high‐penetrance and low‐penetrance variants that contribute to the disease risk 15‐18 . Even though this phenomenon is not widespread, at least according to the current literature, exploring common variants in genes known to harbour high‐penetrance variants in PDAC could still be valuable for understanding the risk of developing PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of this amino acid affects the structure and function of the p53 protein by causing structural modifications 10 . The rs1042522 SNP was investigated for its role in disease risk for the vast majority of common types of cancer, including prostate, breast, and lung cancers [11][12][13] . Another SNP, rs1642785, is found on intron 2 of the TP53 gene and is associated with an increased cancer risk 14 .…”
mentioning
confidence: 99%